Determination of the Accuracy of Thyromental Height Test for Predicting Difficult Laryngoscopy in Obstetric Patients Who Are Candidates for Cesarean Section: An Observational Study - Saghar Samimi Sadeh, MD; Babak Moayer, MD; Masoomeh Natajmajd, MD; Parisa Kianpour, PharmD; Kousha Farhadi, MD; Mahgol Etezadi, PharmD; Mojgan Rahimi, MD; Farhad Etezadi, MD (Current Therapeutic Research)
ABSTRACT: Background: Pregnant women frequently have face and upper airway edema, which makes managing the airways during anesthesia difficult and increases the risk of mask breathing complications and intubation failure. This necessitates an investigation into the sensitivity of various airway tests in predicting difficult intubation. Objective: To assess the accuracy of the thyromental height test (TMHT) in predicting difficult laryngoscopy in obstetric patients undergoing cesarean section and to compare its effectiveness with other airway assessment methods. Methods: We included a cohort of obstetric patients, approved by the Ethics Committee of Tehran University of Medical Sciences, scheduled for elective cesarean sections. During laryngoscopy, preoperative evaluations of the airway were done. The primary aim was to determine the relationship between TMHT (the distance between mentum and the thyroid cartilage) and the Cormack-Lehane (which categories laryngoscopy view from fully observable vocal cords to nonvisible epiglottis) classification, which indicates the level of difficulty in laryngoscopy. Results: After eligibility assessment, 156 patients entered the study, of which 16 had Cormack-Lehane grades III and IV and were considered difficult laryngoscopy. The TMHT demonstrated a higher Matthews correlation coefficient (0.695), sensitivity (0.75), and specificity (0.96) compared with other tests, suggesting that TMHT has the potential to serve as a dependable predictor of challenging laryngoscopy. Conclusions: The use of TMHT can improve patient outcomes and the preoperative evaluation process, making it a valuable tool for anesthesiologists managing obstetric patients. The TMHT could be considered a complementary tool to existing airway assessment methods, particularly in obstetric patients, due to its high predictive accuracy and ease of use.This study is registered at Iranian Registry of Clinical Trial (IRCT) under identifier code of IR.TUMS.SINAHOSPITAL.REC.1399.061.